Implementation of the Centra Learning Based Contextual Learning Model at RA Nurjannah, Tanjung Mulia Village - Siregar, Syukur Madani; Asmoro, Windu; Maqah, Giska Nayla; Syabila, Tiara; Ginting, Zaki Salatin Amin (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The contextual learning model aims to facilitate students' ability to understand and integrate their learning into real life situations in their personal, social and cultural contexts. So they can develop knowledge, creativity and thinking to create their own understanding. The implementation of the learning center-based contextual learning model at RA Nurjannah has gone well. The success of implementing a learning center-based contextual learning model at RA Nurjannah cannot be separated from the factors that influence it, both supporting and inhibiting factors. Therefore, the aim of writing this article is to (1) Identify how to implement the learning center-based contextual learning model at RA Nurjannah and (2) Analyze the supporting and inhibiting factors for implementing the learning center-based contextual learning model at RA Nurjannah. The type of research method used is qualitative research, with descriptive analysis techniques proposed by Miles and Huberman, include interviews, observation and documentation. The subjects of this research are (1) the principal, (2) the deputy principal, and (3) the homeroom teacher RA Nurjannah located in Tanjung Mulia Village, Kec. Merbau Fence, Deli Serdang Regency, North Sumatra. The results of this research show that the implementation of the learning center-based contextual learning model at RA Nurjannah includes: (1) Preparation center, (2) Natural and liquid materials center, (3) Imtaq center, (4) Role playing center, (5) Block center and (6) Music and sports centers. And the supporting and inhibiting factors for the successful implementation of the learning center-based contextual learning model at RA Nurjannah include, supporting factors: (1) The role of the school principal (2) The competence of the school principal, and (3) Completeness of Indoor and Outdoor APE. As well as inhibiting factors: (1) Teachers are less creative, and (2) Weak teacher character.